2017
DOI: 10.1111/trf.14271
|View full text |Cite
|
Sign up to set email alerts
|

Supernatants and lipids from stored red blood cells activate pulmonary microvascular endothelium through the BLT2 receptor and protein kinase C activation

Abstract: Background Although transfusion is a life-saving intervention, it may be associated with significant morbidity in injured patients. We hypothesize that stored red blood cells induce pro-inflammatory activation of human pulmonary microvascular endothelium (HMVECs) resulting in neutrophil (PMN) adhesion and predisposition to acute lung injury (ALI). Methods Ten units of red blood cells (RBCs) were collected and 50% (by weight) were leukoreduced (LR-RBCs) and the remainder was unmodified and stored in additive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 80 publications
(261 reference statements)
1
20
0
Order By: Relevance
“…In agreement with earlier studies, we also found that RBC supernatants possess barrier-disruptive properties (38,46,50,52,56,67). Surprisingly, supernatants from fresh RBCs or old RBCs had same degree of deleterious effects on ECs with that of old RBCs, suggesting that these harmful substances are present in RBC from the beginning, opposing the existing theory that they accumulate during storage.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In agreement with earlier studies, we also found that RBC supernatants possess barrier-disruptive properties (38,46,50,52,56,67). Surprisingly, supernatants from fresh RBCs or old RBCs had same degree of deleterious effects on ECs with that of old RBCs, suggesting that these harmful substances are present in RBC from the beginning, opposing the existing theory that they accumulate during storage.…”
Section: Discussionsupporting
confidence: 90%
“…Many in vitro and in vivo studies suggested possible mechanisms of RBC transfusion-associated pathologies (40,42,68). It was shown that accumulation of bioactive lipids detected in RBC with longer storage duration (49,52) can cause neutrophil activation through a G protein-coupled receptor on the neutrophil (18) and through the leukotriene B4 receptor BLT2 and activation of protein kinase C on pulmonary endothelium (50). Other studies demonstrated the increased production of microparticles from RBC and platelets during storage, which triggered coagulation through tissue factor signaling and induced the secretion of proinflammatory cytokines (11,19).…”
Section: Introductionmentioning
confidence: 99%
“…Histological changes were visualized using the 2-event rat model on H&E stained lung sections (40X) read by a blinded observer. 20,36 PMN sequestration was measured following the first event in flushed, fixed lungs as described. 20,36 Measurement of BALF chemoattractant-1 (CINC-1), Lung Myeloperoxidase (MPO), Liver and Kidney Injury BALF chemokine-induced neutrophil CINC-1 and MPO activity were quantified as described.…”
Section: Histology and Pmn Sequestrationmentioning
confidence: 99%
“…We had hypothesized that early RBC transfusion would be independently associated with fewer organ failure-free days. In preclinical studies, RBC transfusion can contribute to many of the pathophysiologic processes that result in organ dysfunction, including lung injury, renal injury, inflammation, and immune suppression (24)(25)(26)(27)(28)(29)(30)(31). The extent to which RBC transfusion contributes to organ dysfunction in critically ill children remains unclear.…”
Section: Discussionmentioning
confidence: 99%